Isolation And Characterization Of Taro Kolerea Tuber Starch In Sangihe Islands Regency - Adiawan Saudarah; Maria F. Sumual; Henn A. Dien (Sam Ratulangi University, 2023)
This study aims to determine the concentration of NaCl and its interaction with the length of time of isolation of cholerea taro tuber starch, Analyze the physical characteristics of cholerea taro tuber starch, Analyze the proximate composition and oxalate content of cholerea taro tuber. The starch isolation method was designed in a Complete Randomized Design (RAL) with 9 combined treatments of NaCl concentration (%) and soaking time (min). The starch yield of cholerea taro tubers obtained from A1B1 5.97%, A1B2 6.99%, A1B3 7.31%, A2B1 8.09%, A2B2 8.59%, A2B3 9.06%, A3B1 0.42%, A3B2 9.90%, A3B3 10.11%. White Degree L* value ranges from 66.95 - 73.25, A* value ranges from 0.75 - 1.55, B* value ranges from 2.10 - 2.95 and Water Holding capacity (WHC) ranges from 12.04 - 13.43 %. The proximate composition of starch, namely water content ranges from 3.68% - 5.86%, protein content ranges from 0.53% - 0.72% Ash content ranges from 0.34% - 5.67%, Fat content ranges from 0.12% - 0.27%, Starch content 52.31% - 58.56%, Amylose content 22.66% - 22.86% and Oxalate content 24.70% - 47.95%. Isolation of cholerea starch in a 10% NaCl solution combined with a soaking time of 90 minutes is an insulation method that provides the highest amendment of 10.11%. The physical characteristics of the brightness and color of the starch insulation obtained are L* values of 70.10, a* 1.05 and b* 2.50. The resulting water holding capacity is 12.87%. The starch and amylose starch content is 53.27% and 22.68%, with a moisture content of 5.41%, protein 0.69%, ash 5.67%, fat 0.12% and oxalate content 24.70%. Keywords: Isolation, Starch Characterization, Kolerea taro, Sangihe Abstrak Penelitian ini bertujuan untuk Menentukan konsentrasi NaCl dan interaksinya dengan lama waktu isolasi pati umbi talas kolerea, Menganalisis karakteristik fisik pati umbi talas kolerea, Menganalisis komposisi proksimat dan kadar oksalat pati umbi talas kolerea. Metode isolasi pati dirancang dalam Rancangan Acak Lengkap (RAL) dengan 9 perlakuan kombinasi kosentrasi NaCl (%) dan waktu (menit) perendaman. Rendemen pati umbi talas kolerea yang di peroleh dari A1B1 5,97 %, A1B2 6,99 %, A1B3 7,31 %, A2B1 8,09 %, A2B2 8,59 %, A2B3 9,06 %, A3B1 0,42 %, A3B2 9,90 %, A3B3 10,11 %. Derajat Putih Nilai L* berkisar antara 66,95 – 73,25, Nilai a* berkisar antara 0,75 - 1,55, Nilai b* berkisar antara 2,10 – 2,95 dan Water Holding capacity (WHC) berkisar antara 12,04 – 13,43 %. Komposisi proksimat pati yaitu Kadar air berkisar antara 3,68 % - 5,86%, kadar protein berkisar antara 0,53 % - 0,72 % kadar Abu berkisar 0,34 % - 5,67 %, kadar Lemak berkisar antara 0,12 % - 0,27 %, kadar Pati 52,31 % - 58,56%, kadar Amilosa 22,66 % - 22,86 % dan kadar Oksalat 24,70 % - 47,95 %. Isolasi pati kolerea dalam larutan NaCl 10% dikombinasikan dengan lama waktu perendaman 90 menit merupakan cara isolasi yang memberikan rendemen tertinggi yaitu 10,11 %. Karakteristik fisik yaitu kecerahan dan warna isolasi pati yang diperoleh adalah Nilai L* 70,10, a* 1,05 dan b* 2,50. Water holding capacity yang dihasilkan adalah 12,87 %. Kadar pati dan amilosa pati adalah 53,27 % dan 22,68 %, dengan kadar air 5,41 %, protein 0,69 %, abu 5,67 % , lemak 0,12 % dan kadar oksalat 24,70 %. Kata kunci : Isolasi, Karakterisasi Pati, Talas Kolerea, Sangihe